(untitled) (Itinera, 2024)
The aim of this paper is to describe in an introductory way the debate that was generated when digital culture emerged in the 1990s with the advent of the Web. It is possible to trace a genaology of values and aesthetic implications that produced at least two major factions: the nihilists and the humanists. Digital culture, yet another frontier of technological progress, was thus interpreted both as a critical erosion of content and as a possibility of collective development for humanity. The paper traces some famous positions (e.g. Bolter, Lévy, De Kerckhove, Flusser, Baudrillard) with the only purpose of mapping this debate that in fact leads back once again to the great Western theme of representation, mimesis.